Promoter-specific trans activation and repression by human cytomegalovirus immediate-early proteins involves common and unique protein domains. - Stenberg, R M (1990)
trans activation of promoters by viral regulatory proteins provides a useful tool to study coordinate control of gene expression. Immediate-early (IE) regions 1 and 2 of human cytomegalovirus (CMV) code for a series of proteins that originate from differentially spliced mRNAs. These IE proteins are proposed to regulate the temporal expression of the viral genome. To examine the structure and function of the IE proteins, we used linker insertion mutagenesis of the IE gene region as well as cDNA expression vector cloning of the abundant IE mRNAs. We showed that IE1 and IE2 proteins of CMV exhibit promoter-specific differences in their modes of action by either trans activating early and IE promoters or repressing the major IE promoter (MIEP). Transient cotransfection experiments with permissive human cells revealed a synergistic interaction between the 72- and the 86-kilodalton (kDa) IE proteins in trans activating an early promoter. In addition, transfection studies revealed that the 72-kDa protein was capable of trans activating the MIEP. In contrast, the 86-kDa protein specifically repressed the MIEP and this repression was suppressed by the 72-kDa protein. Furthermore, observations based on the primary sequence structure revealed a modular arrangement of putative regulatory motifs that could either potentiate or repress gene expression. These modular domains are either shared or unique among the IE proteins. From these data, we propose a model for IE protein function in the coordinate control of CMV gene expression.